STRUCTURE AND DIVERSITY OF THE ARBOREAL COMPONENT IN CERRADO SENSU STRICTO IN NORTHERN MINAS GERAIS - Lima, Priscila Mendes; Arruda, Daniel Meira; Fonseca, Rúbia Santos; Silva, Deicy Danielle (Floresta, 2020)
Due to a rapid change in the land use in northern Minas Gerais State, southeastern Brazil, large amounts of cerrado have been converted into crops. There is little information about the structure and diversity of the remaining communities in the region. The present study aimed to characterize the structure of the tree vegetation in a cerrado sensu stricto area. We delimited thirty 20m x 20m plots and sampled tree individuals with diameter equal to or greater than 4.8 cm at 30 cm from the ground level (DGH30). We sampled a total of 2616 individuals of 76 species and 33 botanical families. The community showed a density of 2180 ind/ha and a basal area of 17.3 m2/ha. Qualea grandiflora, Terminalia fagifolia, and Dimorphandra mollis showed high importance values. Standing dead individuals stood out in the community. The Shannon diversity index (3.10) and Pielou’s evenness (0.70) indicate that the community is in an intermediate stage of succession in comparison with others. Despite the signs of disturbance, the community still includes species of great social and economic importance for the local population. This community’s floristic and structural patterns can be used to reference extractive management, restoration, and conservation initiatives of other cerrado areas in the region.